Utilization of Fly Ash and Rice Husk as Chromium Metal Adsorbent in Batik Waste - Herawati Oktavianty; Sunardi Sunardi; Khairul Amri (Universitas Ahmad Dahlan, 2022)
This study aims to produce adsorbents from fly ash boilers for palm oil mills and rice husk ash as adsorbents for batik waste. The research design used was Complete Block Design with 2 factors, namely the ratio of rice husk ash mass to fly ash boiler with 3 levels, namely A1 (25%:75%), A2 (50%:50%), A3 (75%:25%), and the concentration factor of HCl with 3 levels, namely B1 (1M); B2 (2M), B3 (3M), which is done 2 times repetition. The experimental stages include boiler fly ash pretreatment, rice husk ash pretreatment, synthesis and activation of adsorbents and adsorption tests on batik wastewater. Furthermore, analysis of COD, TSS and chromium was carried out. The results showed that the A3B2 sample provided optimal adsorption capacity for the analysis of COD, TSS and Chrom metal with values of 57.62 mg/L, 1.43 mg/L and 3.24 ppm, respectively, where there was a decrease in COD of 74%, a decrease in TSS of 97.56% and a decrease in chrom metal ion of 80.43%. This is due to the use of more rice husk ash with the use of HCl solution as an activator can increase the silica active group on the adsorbent thereby increasing the surface area of the adsorbent, where the surface area of the A3B2 sample is 118.24 m2/g.